The Treatment of Congenital Recto-vestibular Fistula and Recto-perineal Fistula, and the Effects of the Megarectum on Defecation - Li, Jian; Dai, Jinyu; Wu, Xiaoxia; Sun, Xiaobing (Current Medical Imaging, 2024)
Objective This study aims to discuss the treatment of congenital recto-vestibular fistula and recto-perineal fistula, and the effect of the megarectum on defecation. Background Congenital recto-vestibular fistula or recto-perineal fistula is the most common type of anorectal malformation, and surgical methods include posterior sagittal anorectoplasty, anterior sagittal anorectoplasty, and mid-sagittal anorectoplasty, which can be performed at stage one or stage two after the ostomy. In the later stages of a recto-vestibular fistula, constipation is a common complication. Rectal dilatation is frequently associated with constipation, and the effect of rectal dilatation on defecation should be discussed for patients with congenital recto-vestibular or recto-perineal fistula who had rectal dilatation prior to surgery. Rectal dilatation may be one of the causes of constipation for congenital recto-vestibular fistula and recto-perineal fistula. Methods The patients in this study were 67 children with congenital recto-vestibular fistula or recto-perineal fistula treated in our hospital from March 2013 to February 2017. All patients underwent an MRI of the spine and a barium enema. Six patients with myelodysplasia and sacral agenesis were excluded from this study. There were 18 patients with rectal dilatation (ages: 4-month-old to 1 year old, male: 3, female: 15). Seven of them had anterior sagittal anorectoplasty (group A), and 11 had anorectoplasty with dilated rectum resection (group B). Forty-three patients (ages: 3- to 10 months old, male: 6; female: 37) without a dilated rectum underwent anterior sagittal anorectoplasty (group C). Results All patients were followed up for 1 year to 5 years. Among the 50 patients who had undergone an anoplasty, 5 out of 7 patients with rectal dilatation developed post-operative constipation, and 3 of them had normal defecation after the second resection of the dilated rectum. Only two out of 43 patients without rectal dilatation developed post-operative constipation. One out of 11 patients with rectal dilatation who underwent anoplasty and resection of the dilated rectum developed post-operative constipation. Conclusion Patients with congenital recto-vestibular fistula or recto-perineal fistula complicated by rectal dilatation are more susceptible to post-operative constipation. Resection of the dilated rectum at the same time can reduce the incidence rate of constipation. A barium enema should be performed pre-operatively for patients with congenital recto-vestibular fistula or recto-perineal fistula. If the dilated rectum is found, it can be resected at the same time.
Keywords: Malformation